People, states & fear an agenda for international security studies in the post-cold war era - Buzan, Barry (ECPR Press, 2007)
This widely acclaimed book examines how states and societies pursue freedom from threat in an environment in which competitive relations are inescapable across the political, economic, military, societal and environmental landscapes. Throughout, attention is placed on the interplay of threats and vulnerabilities, the policy consequences of overemphasising one or the other, and the existence of contradictions within and between ideas about security. Barry Buzan argues that the concept of security is a versatile, penetrating and useful way to approach the study of international relations. Security provides an analytical framework between the extremes of power and peace, incorporates most of their insights - and adds more of its own. People, States & Fearis essential reading for all students and researchers of international politics and security studies. 25th Anniversary Edition: A new introduction, placing this classic text in a current context, was added to this book by the author in 2007.